Laddu is born: chumchum: oxford - Rumana, Husain; Akbar, Zia Ayesha, Tariq Rimsha, Shakeel Shakir, Khan (Oxford University Press Karachi, 2015)
Laddu Paida Hua! is about the celebration of the birth of a baby monkey called Laddu.